2022
DOI: 10.1093/ndt/gfac018
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous immunization with BNT162b2 followed by mRNA-1273 in dialysis patients: seroconversion and presence of neutralizing antibodies

Abstract: Introduction The vital renal replacement therapy makes it impossible for dialysis patients to distance themselves socially. This results in a high risk of SARS-CoV-2 infection and developing COVID-19 with excess mortality due to disease burden and immunosuppression. We determined the efficacy of a 100 µg booster of mRNA-1273 (Moderna, Inc., Cambridge, Massachusetts, USA) 6 months after two doses of BNT162b2 (BioNTech/Pfizer, Mainz, Germany/New York, NY, USA) in 194 SARS-CoV-2 naïve dialysis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
(39 reference statements)
2
11
0
Order By: Relevance
“…These studies showed a booster effect of variable size in the two group populations. Among KTR who failed to develop detectable antibodies after the second vaccine dose, the percentage of responders after 3D varied substantially across the studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Fewer studies have assessed the impact of the receipt of 3D on SARS-CoV-2-S-targeted functional T-cell responses [5,[18][19][20][21][22], which crucially contribute to providing protection against SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed a booster effect of variable size in the two group populations. Among KTR who failed to develop detectable antibodies after the second vaccine dose, the percentage of responders after 3D varied substantially across the studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Fewer studies have assessed the impact of the receipt of 3D on SARS-CoV-2-S-targeted functional T-cell responses [5,[18][19][20][21][22], which crucially contribute to providing protection against SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Our research in hemodialysis patients demonstrated a strong vaccinal nAb response to MOD-MOD-MOD and an even stronger one post-COVID-19. Although plaque reduction neutralization test (PRNT) is the preferred method for quantifying antibodies capable of neutralizing SARS-CoV-2 virus, multiple groups had extensively evaluated GenScript SARS-CoV-2 Surrogate Virus Neutralization Test Kit (6,(14)(15)(16). It was demonstrated that GenScript sVNT ELISA method gives comparable results and good correlation to PRNT in the detection of nAbs.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several strengths. First, while previous reports addressed the nAb response to various homologous and heterologous triple vaccination schemes (6)(7)(8)(9)12), this is the first regarding nAb dynamics after MOD-MOD-MOD vaccination. Second, we quantitated in the same serum sample the nAb responses specific to both WT and Omicron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By correlating the SARS-CoV-2 antibody concentrations with the inhibitory power for binding of the wild-type spike protein to the ACE-2 receptor, we derived a cutoff value for a 30% virus neutralization that may be clinically meaningful for patients after kidney transplantation (Figure 3 ). The cutoff value largely corresponds to that in a recently examined dialysis cohort 13 and in the normal population as provided by the manufacturer. 14 However, not entirely unexpectedly and as far as comparable because 2 different test methods were used, the respective cutoff on basis of the live virus neutralization test for inactivation of the Omicron variant was 53 times higher.…”
Section: Discussionmentioning
confidence: 99%